2020
DOI: 10.46545/aijbms.v2i1.158
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Affecting Supplier Relationship Management in the Food Manufacturing Small and Medium Enterprises (SMEs) in Dar es Salaam Tanzania

Abstract: The Tanzanian food industry is one of the most critical sectors in the country. Small and medium enterprises (SMEs) are the largest processors of food. Although SMEs mostly deal with processing food, they still face challenges, especially with their suppliers. Though previous researchers have investigated partnership issues in SMEs, little has been reported on the factors that impact the supplier relationships found in food manufacturing SMEs. This study employed a qualitative design where semi-structured inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 25 publications
4
31
0
Order By: Relevance
“…The results of the quality assessment and supplier certifications were not always positive [ 47 , 57 ]. However, a study from Tanzania showed that in some regions poor-quality materials were rarely mentioned as a barrier to supplier relationship management [ 32 ]. The PCA and Spearman’s calculations of this study’s results showed the large impact of certification on supplier evaluation rating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the quality assessment and supplier certifications were not always positive [ 47 , 57 ]. However, a study from Tanzania showed that in some regions poor-quality materials were rarely mentioned as a barrier to supplier relationship management [ 32 ]. The PCA and Spearman’s calculations of this study’s results showed the large impact of certification on supplier evaluation rating.…”
Section: Discussionmentioning
confidence: 99%
“…In general, there are not many publications dealing with the evaluation of suppliers for the food industry manufacturers. In a few studies, suppliers were assessed on the risk of cooperation [16,[30][31][32]. The evaluation criteria concerned supplier selection and supervision [10,[33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…However, findings are inconsistent with [20], who found an insignificant association between individualism and entrepreneurial values. Moreover, lack of capital has been acknowledged as one of the challenges hindering entrepreneurial opportunity exploitation in Tanzania [26,27]. Therefore, some form of collectivism is required to raise capital from family and friends for the exploitation of entrepreneurial opportunities.…”
Section: Hypotheses Testing On Both Direct and Indirect (Mediation) E...mentioning
confidence: 99%
“…A well-built learning culture may keep the firm abreast of customer desires, competitor activities, employees' actions and suppliers behaviours; the information that assists in developing and modifying business practices. Yuan, Feng, Lai and Collins (2018) established that Accordingly, it is considered important for business owner-managers to have the right learning orientation for building competitive advantage, especially in an uncertain and turbulent business environment (Bengesi & Le Roux 2014b;Yuan, Feng, Lai & Collins, 2018;Nkwabi & Fallon, 2020). Learning orientation is regarded as one of the strategic resources that shape the operations of a firm in the marketplace (Dukeov, Bergman, Heilmann & Nasledov, 2020).…”
Section: The Concept Of Learning Orientationmentioning
confidence: 99%